2008
DOI: 10.1007/s10803-008-0566-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Improvisational Music Therapy on Joint Attention Behaviors in Autistic Children: A Randomized Controlled Study

Abstract: The purpose of this study was to investigate the effects of improvisational music therapy on joint attention behaviors in pre-school children with autism. It was a randomized controlled study employing a single subject comparison design in two different conditions, improvisational music therapy and play sessions with toys, and using standardized tools and DVD analysis of sessions to evaluate behavioral changes in children with autism. The overall results indicated that improvisational music therapy was more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
245
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 277 publications
(302 citation statements)
references
References 29 publications
(21 reference statements)
18
245
1
16
Order By: Relevance
“…Five studies featured multiple baseline single-group design, with a fewer number of participants ranging from two to six per study (Franco et al, 2013;Jones et al, 2006;Martins & Harris, 2006;Rocha et al, 2007;Vismara & Lyons, 2007). (Franco et al, 2013;Gulsrud et al, 2007;Jones et al, 2006;Kim et al, 2008Kim et al, , 2009Lawton & Kasari, 2012a, 2012bMartins & Harris, 2006;Schertz et al, 2013;Vismara & Lyons, 2007;Wong, 2013); response to JA and overall JA behaviors (Kasari et al, 2010;Kim et al, 2008;Rocha et al, 2007;Schertz et al, 2013;Wong, 2013); and initiating JA skills (Franco et al, 2013;Ingersoll, 2012;Jones et al, 2006;Kaale et & Kasari, 2012b;Rocha et al, 2007;Schertz et al, 2013;Vismara & Lyons, 2007;Yoder & Stone, 2006 (Chiang et al, 2016;Jones et al, 2006;Kasari et al, 2010;Rocha et al, 2007;Vismara & Lyons, 2007). Similar findings indicate that teachers of children living with ASD can effectively elicit JA skills in classroom settings following targeted intervention training from interventionists (Kaale et al, 2012;Lawton & Kasari, 2012b;…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Five studies featured multiple baseline single-group design, with a fewer number of participants ranging from two to six per study (Franco et al, 2013;Jones et al, 2006;Martins & Harris, 2006;Rocha et al, 2007;Vismara & Lyons, 2007). (Franco et al, 2013;Gulsrud et al, 2007;Jones et al, 2006;Kim et al, 2008Kim et al, , 2009Lawton & Kasari, 2012a, 2012bMartins & Harris, 2006;Schertz et al, 2013;Vismara & Lyons, 2007;Wong, 2013); response to JA and overall JA behaviors (Kasari et al, 2010;Kim et al, 2008;Rocha et al, 2007;Schertz et al, 2013;Wong, 2013); and initiating JA skills (Franco et al, 2013;Ingersoll, 2012;Jones et al, 2006;Kaale et & Kasari, 2012b;Rocha et al, 2007;Schertz et al, 2013;Vismara & Lyons, 2007;Yoder & Stone, 2006 (Chiang et al, 2016;Jones et al, 2006;Kasari et al, 2010;Rocha et al, 2007;Vismara & Lyons, 2007). Similar findings indicate that teachers of children living with ASD can effectively elicit JA skills in classroom settings following targeted intervention training from interventionists (Kaale et al, 2012;Lawton & Kasari, 2012b;…”
Section: Resultsmentioning
confidence: 67%
“…It was determined that all of the remaining studies in this analysis are classified as Level I, II, or III based on the AOTA evidence standards (AOTA, 2012). Of the 19 included studies, a majority (n = 13) featured randomized controlled trial (RCT) designs with subject numbers ranging from 10 to 61, with an average of 37 participants across all RCTs (Gulsrud et al, 2007;Ingersoll, 2012;Kaale et al, 2012;Kasari et al, 2006Kasari et al, , 2010Kim et al, 2008Kim et al, , 2009Lawton & Kasari, 2012a, 2012bSchertz et al, 2013;Wong, 2013;Wong et al, 2007;Yoder & Stone, 2006). One study featured a non-randomized controlled trial design, with an equivalent sample size of 34 participants (Chiang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2006 Cochrane review of music therapy in ASD concluded that music therapy was "superior to 'placebo' therapy with respect to verbal and gestural communicative skills," but effects on behavior were not significant; the authors noted also that the studies were of "limited applicability to clinical practice" and that more research is needed to establish whether the effects of music therapy are lasting. 47 Two recent randomized controlled studies, by the same researchers, 48,49 used a single-subject comparison design to compare improvisational music therapy to play sessions with toys. They found the intervention superior to play at facilitating joint attention behaviors, nonverbal social communication skills, more and longer events of "joy," "emotional synchronicity," and "initiation of engagement" behaviors in children, and a phenomenon that the authors described as "more yes, less no."…”
Section: Mind-body Medicinementioning
confidence: 99%